Uso de un aditivo a base de Cantaxantina y extracto de Achiote (bixa orellana l.) en dietas de gallinas de postura y su efecto sobre la coloración de la yema y la vida de anaquel del huevo. - Rojas Vera, Víctor Roberto (2014)
This study aimed to evaluate the use of an additive canthaxanthin based and annatto extract (Bixa orellana L.) in diets of laying hens and its effect on the color of the yolk and egg shelf life. 864 hens were used 34 to 45 weeks old. The treatments were T0 (control diet), T1 (T0 + 30 g of canthaxanthin and annatto extract) and T2 (T0 + 60 g of canthaxanthin and annatto extract), distributed in a completely randomized design with 6 replicates per treatment. Yielding for egg production 88.636, 91.933 and 90.823 % weight egg 60.525, 61.659 and 61.543 g, egg mass of 53.634, 56.435 and 55.754 g, coloring yolk by Roche method temperature of 22 °C was 6, 9 and 12 and temperature of 7 °C was 6, 9 and 12, by the method photocolorimetric minolta a temperature of 22 °C was for "L" of 45.63, 43.84 and 42.64, for "a" of 0.18, 3.79 and 6.66 and "b" of 21.82, 20.57 and 20.15 and temperature of 7 °C was for "L" of 42.10, 40.24 and 39.65; for "a" of 0.07, 3.68 and 6.44 and for "b" of 19.35, 18.36 and 18.18, the shelf life at room temperature of 22 °C was 78, 82 and 86 and temperature of 7 °C was 81, 86 and 90 UH. Lipid peroxidation by MDA-TBARS method was 0.106, 0.078 and 0.050 umol MDA/g yolk, for T0, T1 and T2 respectively. All variables listed above statistically significant differences between treatments (P < 0.05) were found. Food consumption was 103,977, 109,292 and 107,523 g and feed conversion of 1.940, 1.938 and 1.928. It is concluded that the addition of canthaxanthin and annatto extract at 30 and 60 g/t compared to the control, improved performance parameters, yolk color and egg Shelf Life.